Extension of the Periods for Consent to and Payment of Quota Increases. - International Monetary Fund. Finance Dept. (Washington, D.C. : International Monetary Fund, 2019)
This paper proposes a further six-month extension of the period for members to consent to an increase in their quotas under the Fourteenth General Review of Quotas ("Fourteenth Review") through June 28, 2019.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Board Of Governors Resolution No. 66-2; Payment Of Quota Increase; Payment Period; PP; Quota Payment; Syrian Arab Republic